Re-establishment of Stylosanthes gracilis (Leguminosae) at species level - Calles, T; Schultze-Kraft, Rainer (Springer, 2010)
In most taxonomic revisions of Stylosanthes Sw., Stylosanthes gracilis Kunth has been regarded as a variety or even a synonym of S. guianensis (Aubl.) Sw. This has created considerable confusion among scientists working with the latter species which is an agriculturally important tropical forage and cover legume. This study collected taxonomically relevant evidence, for evaluating S. gracilis as a valid species. Since the type specimen is lost, a collection from the same location as the original type is proposed here as a neotype.